THE HUMAN BOTTOM OF NON-HUMAN THINGS: ON CRITICAL THEORY AND ITS CONTRIBUTIONS TO CRITICAL DISABILITY STUDIES - Burghardt, Madeline (Critical Disability Discourses, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Critical theory has potential application to several points of interrogation within the critical disability studies canon. While some disability theorists have made use of the analyses offered by critical theory, possible areas of contribution remain. In this article, following an historical overview which traces some of the fundamental developments in the critical theory canon, three areas of analysis are examined in light of their potential to broaden and interrogate current critical disability theory. These include the sense of moral obligation characteristic of early contemporary critical theorists, particularly from the Frankfurt school; materialism and the link between disability and economic means of production, including materialist links to socio-psychic explorations of disability; and connections between current understandings of disability and cultural aesthetic concerns.